Réponses

2012-11-25T19:42:04+01:00

A = 3( x -10)(x + 10) + (2x + 5)(x + 10)

A= 3 ( x² +10x -10x -100) + 2x² +20x +5x +50

A = 3( tu calcules dans la parenthèse) cela fait x² -100) + 2x² +25x + 50

A = tu appliques la distributivité 3 X (x² - 100) + 2x² +25x + 50

A = 3x² - 300 + 2x² + 25x + 50

A = 5 x² + 25x  -250

 

B= 4(3x+6)(5x+1) -2 (3x-6)²

B = 4( 15x² +3 +30 +3x) -2 (3x -6) (3x -6)

B= 4 ( 15x² +3x +33) -2 ( 9x² -18x -18x +36)

B= (60x² +12x + 132) -2 ( 9x² -36x +36)

B= 60x² + 12x + 132 - 18x² + 72x +72

B= 42 x² + 84x + 204

 

C= 4(7x+5)² +4 ( 2x -1)(7x+5)

C= 4 (49x² +24 x +25) +4 ( 14 x² +14x -7 -5)

C= 4 ( 49x² +24x +25) +56 x² + 56x -48)

C= 196 x² +96x +25 +56x² + 56x -48

C= 252 x² + 152 x -23